Forces of academic innovation / Tengku Intan Suzila Tengku Sharif and Mohd Yusri Mohamad Noor - Tengku Sharif, Tengku Intan Suzila; Mohamad Noor, Mohd Yusri (2010)
Innovation in teaching and learning desires more than just creativity and a handful of empathy. It cries for inter-chained forces to ensure noble justice proliferate to the grass roots as the heart and soul to an academic innovation are the future leaders. Its notification and executions need to be right at first attempt. This paper tries to discuss the key concepts to academic innovation, value and executions by means of secondary sources reviews and in the end an academic innovation model is suggested. Lastly, words of advice from pioneering innovators summarize the discussion.